Results from the CLUES study: a cluster randomized trial for the evaluation of cardiovascular guideline implementation in primary care in Spain - Arritxu Etxeberria; Idoia Alcorta; Itziar Pérez; Jose Ignacio Emparanza; Elena Ruiz de Velasco; Maria Teresa Iglesias; Rafael Rotaeche (BMC, 2018)
Abstract Background The implementation of evidence-based clinical practice guidelines (CPG) can improve patients care. To date, the impact of implementation strategies has not been evaluated in our context. This study is aimed to evaluate the effectiveness of a multifaceted tailored intervention targeting clinician education for the implementation of three cardiovascular risk-related CPGs (type 2 diabetes, hypertension and dyslipidemia) in primary care at the Basque Health Service compared with usual implementation. Methods We conducted a cluster randomized controlled trial in two urban districts with 43 primary care units (PCU). Data from all patients diagnosed with diabetes, hypertension and all those eligible for coronary risk (CR) assessment were included. In the control group, guidelines were introduced in the usual way (by email, intranet and clinical meetings). In the intervention group, the implementation also included a specific website and workshops. Primary endpoints were annual HbA1c testing (diabetes), annual general laboratory testing (hypertension) and annual CR assessment (dyslipidemia). Secondary endpoints were process, prescription and clinical endpoints related with guideline recommendations. Analysis was performed at a PCU level weighted by cluster size. Results Significant differences between groups were observed in primary outcomes in the dyslipidemia CPG: increased CR assessment for both women and men (weighted mean difference, WMD, 13.58 and 12.91%). No significant differences were observed in diabetes and hypertension CPGs primary outcomes. Regarding secondary endpoints, annual CR assessment was significantly higher in both diabetic and hypertensive patients in the intervention group (WMD 28.16 and 27.55%). Rates of CR assessment before starting new statin treatments also increased (WMD 23.09%), resulting in a lower rate of statin prescribing in low risk women. Diuretic prescribing was higher in the intervention group (WMD 20.59%). Clinical outcomes (HbA1c and blood pressure control) did not differ between groups. Conclusions The multifaceted implementation proved to be effective to increase the CR assessment and to improve prescription, but ineffective to improve diabetes and hypertension related outcomes. In order to obtain real improvements when cardiovascular issues are tackled, perhaps other or additional interventions need to be implemented besides education of professionals. Trial registration Current Controlled Trials, ISRCTN 88876909 (retrospectively registered on January 13, 2009)